2005
DOI: 10.1111/j.0014-3820.2005.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Inference of a Radiation in Mastus (Gastropoda, Pulmonata, Enidae) on the Island of Crete

Abstract: The Mediterranean land snail genus Mastus (Beck, 1837) is highly divergent. Thirty-two Mastus species have been recorded throughout the genus range, and 23 of them are endemic to the islands of the Aegean Sea and mainland Greece. Of these, all 16 Mastus species reported from Crete are endemic to this island. A robust molecular phylogenetic framework based on mitochondrial and nuclear genes (1623 bp) allowed us to explore the temporal diversification pattern of lineages, using molecular clock approaches. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 73 publications
3
44
1
1
Order By: Relevance
“…The accelerated mtDNA evolution hypothesis was supported by the findings in some taxa [24], [26], [27], [28], but not in others [29], [30], [31], whereas a hypothesis was formulated, on developmental grounds, to account for the extraordinary mtDNA diversity in mollusks [32]. At the same time, several studies concluded that a history of allopatric divergence followed by secondary contact (hypothesis ii) could explain sympatry of diverse haplotypes [24], 30,31,33,34,35,36. The effect of natural selection in shaping the population genetic structure of pulmonates (hypothesis iii) has not been directly investigated, but there were cases where natural selection was considered to have played a major role [33], [37], [38].…”
Section: Introductionmentioning
confidence: 96%
“…The accelerated mtDNA evolution hypothesis was supported by the findings in some taxa [24], [26], [27], [28], but not in others [29], [30], [31], whereas a hypothesis was formulated, on developmental grounds, to account for the extraordinary mtDNA diversity in mollusks [32]. At the same time, several studies concluded that a history of allopatric divergence followed by secondary contact (hypothesis ii) could explain sympatry of diverse haplotypes [24], 30,31,33,34,35,36. The effect of natural selection in shaping the population genetic structure of pulmonates (hypothesis iii) has not been directly investigated, but there were cases where natural selection was considered to have played a major role [33], [37], [38].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the distribution areas of the originating species should be similar and should form distinct geographic clusters. There are radiations of other land snail groups on Crete, e.g., of Mastus [62]–[63], Orculella [64], and Albinaria [65]–[68]. A statistical test indicated that the distribution areas of 74 endemic land snail species belonging to genera with at least two endemic species are not significantly clustered [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high positive correlation between sexual isolation and genetic divergence is predicted when sympatry prevails (Coyne & Orr, 1989, 1997 and for strongly sexual dimorphic taxa where there is a more important role for sexual selection (Mendelson, 2003). Although, sexual selection is a potential cause of speciation in land snails (Charnov, 1979;Schilthuizen, 2003;Parmakelis et al, 2005), its significance for hermaphrodites is disputed (Greeff & Michiels, 1999), and empirical evidence is still lacking. Therefore, more studies on hermaphroditic organisms are necessary to confirm whether they are exceptional for the evolution of sexual isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of correlation between the current geographic distances and sexual isolation and genetic divergence is expected as the area of distribution of Albinaria, and particularly the Aegean archipelago, has a complex palaeogeographic history (Meulenkamp, 1985), where erratic vicariant events prevail and not isolation by distance processes. Several studies (Douris et al, 1995(Douris et al, , 1998aBeerli et al, 1996;Chatzimanolis et al, 2003;Poulakakis et al, 2003Poulakakis et al, , 2005Kasapidis et al, 2005;Parmakelis et al, 2005), suggest that the present, often mosaic, distribution of most of the terrestrial Aegean taxa, is mainly shaped through vicariant phenomena resulting from the complex geological history of the east Mediterranean and especially of the Aegean archipelago. Furthermore, long-distance dispersal over sea is also involved (Douris et al, 1998a;Dennis et al, 2000;Kasapidis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%